2022
DOI: 10.1111/ene.15233
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal dynamic brain activity and functional connectivity of primary motor cortex in blepharospasm

Abstract: Background and purpose: Accumulating evidence indicates that dynamic amplitude of low-frequency fluctuations (dALFF) or dynamic functional connectivity (dFC) can provide complementary information, distinct from static amplitude of low-frequency fluctuations (sALFF) or static functional connectivity (sFC), in detecting brain functional abnormalities in brain diseases. We aimed to examine whether dALFF and dFC can offer valuable information for the detection of functional brain abnormalities in patients with ble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…It is a novel metric reflecting the changes in ALFF over time. dALFF describes the temporal fluctuation in energy expenditure based on the oxygen level and reflects the plasticity and flexibility of spontaneous brain activity [27,28]. DALFF likely captures useful information missed in sALFF, and can therefore provide complementary information [27].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is a novel metric reflecting the changes in ALFF over time. dALFF describes the temporal fluctuation in energy expenditure based on the oxygen level and reflects the plasticity and flexibility of spontaneous brain activity [27,28]. DALFF likely captures useful information missed in sALFF, and can therefore provide complementary information [27].…”
Section: Introductionmentioning
confidence: 99%
“…dALFF describes the temporal fluctuation in energy expenditure based on the oxygen level and reflects the plasticity and flexibility of spontaneous brain activity [27,28]. DALFF likely captures useful information missed in sALFF, and can therefore provide complementary information [27]. Chen et al [29] found that the dALFF values of the bilateral anterior insula, bilateral orbitofrontal cortex, bilateral medial prefrontal cortex, bilateral anterior cingulate cortex (ACC), and left middle frontal gyrus cortex were significantly lower in patients with migraine without aura compared with HC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All these three functions are impaired in MS patients since the eyelids spasm or apraxia of eyelids opening can interfere with their visuospatial ability and attention, and then influence the motor comprehension and motor planning. Moreover, Luo et al (2022) found lower dynamic FC between the lobule VIII and the primary motor cortex in blepharospasm patients compared to HCs and hemifacial spasm patients, and from this, they claimed that lobule VIII might play a crucial role in triggering the development of blepharospasm. All the evidence verifies the motor role of lobule VIII in MS.…”
Section: Discussionmentioning
confidence: 93%
“…The ponto-cerebello-thalamo-cortical motor circuit plays a crucial role in controlling the blink reflex and coordinating eyelid movements. Earlier fMRI studies have shown that focal dystonia is closely related to the ponto-cerebello-thalamo-cortical circuit dysfunction 35. Alterations in the thalamus have been a hot issue in HFS, and several studies have shown structural, functional, and metabolic abnormalities in the thalamus of HFS patients 6,16,19,36.…”
Section: Discussionmentioning
confidence: 99%